Why does ammonia not freeze out in the centre of pre-stellar cores?. Issue 1 (16th May 2019) - Sipilä, O; Caselli, P; Redaelli, E; Juvela, M; Bizzocchi, L
Abstract: We carried out a parameter-space exploration of the ammonia abundance in the pre-stellar core L1544, where it has been observed to increase toward the centre of the core with no signs of freeze-out onto grain surfaces. We considered static and dynamical physical models coupled with elaborate chemical and radiative transfer calculations, and explored the effects of varying model parameters on the (ortho + para) ammonia abundance profile. None of our models are able to reproduce the inward-increasing tendency in the observed profile; ammonia depletion always occurs in the centre of the core. In particular, our study shows that including the chemical desorption process, where exothermic association reactions on the grain surface can result in the immediate desorption of the product molecule, leads to ammonia abundances that are over an order of magnitude above the observed level in the innermost 15 000 au of the core – at least when one employs a constant efficiency for the chemical desorption process, irrespective of the ice composition. Our results seemingly constrain the chemical desorption efficiency of ammonia on water ice to below 1 per cent. It is increasingly evident that time-dependent effects must be considered so that the results of chemical models can be reconciled with observations.